The influence of parenting practices and parental presence on children's and adolescents' pre-competitive anxiety - Bois, J. E.; Lalanne, J.; Delforge, C. (Journal of Sports Sciences, 2009)
We examined parental influence on athletes' pre-competitive anxiety. The effect of parental presence during competition was studied as was the role of parenting practices. Data were collected from a sample of 341 athletes (201 basketball players and 140 tennis players) before an official competition. Analysis of variance indicated that the presence of both parents was associated with higher pre-competitive anxiety for all participants, except male tennis players. The absence of both parents did not result in less anxiety. A second analysis of variance revealed that females tennis players at provincial and national level perceived greater parental pressure than most other participants. Canonical correlation analysis showed a positive relationship between pre-competitive anxiety and parenting practices for tennis players, but not for basketball players. Directive behaviours and pressure were positively associated with pre-competitive anxiety for all tennis players, whereas praise and understanding was negatively related to anxiety for female tennis players only.